Responsabilidad social corporativa y reputación corporativa en el sector financiero de países en desarrollo - Lizarzaburu, Edmnundo R. (2016)
The article proposes a theoretical model that relates corporate social responsibility and corporate reputation in order to hypothesizing influence on investor confidence by studying and usinig cases of financial firms in Peru. the case study method is used to analyze four Peruvian banks accounting for 25% of all participants of the banking system in Peru and 80% in the participation of three financial indicators: % credits, % deposits and % Patrimony. Peruvian banking companies have improved their reputation for social responsibility actions. This improved reputation has been correlated with a strengthening of the value of the company. Furthermore, analysis of each case, framed in CSR plans generates seven propositions classified in three relationships (CSR and investor confidence, CSR and corporate reputation and corporate reputation and investor confidence). In future studies, we intend to extend this analysis with large samples of Peruvian companies have developed CSR practices. The novelty of this work is twofold. The literature has analyzed the concepts of CSR and RC isolation. After a thorough review a model that relates the two concepts is proposed. Second, the model is used to hypothesize CSR and CR relationship in financial sector companies in developing countries. The research on this topic has been conducted mainly in production companies and developed countries.